2020
DOI: 10.1021/acsami.0c14777
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Electrodeposition of Few-Layer MoS2 on Graphene for 2D Material Heterostructures

Abstract: Heterostructures involving two-dimensional (2D) transition metal dichalcogenides and other materials such as graphene have a strong potential to be the fundamental building block of many electronic and opto-electronic applications. The integration and scalable fabrication of such heterostructures is of essence in unleashing the potential of these materials in new technologies. For the first time, we demonstrate the growth of few-layer MoS2 films on graphene via non-aqueous electrodeposition. Through methods su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
(163 reference statements)
0
26
1
Order By: Relevance
“…In previous works, we characterized the material composition of MoS 2 films electrodeposited via similar electrochemical environments using wavelength dispersive X‐ray spectroscopy (WDX) and X‐ray photoelectron spectroscopy (XPS). [ 7,8 ] These results have shown that the Mo:S ratio is ≈1:2.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…In previous works, we characterized the material composition of MoS 2 films electrodeposited via similar electrochemical environments using wavelength dispersive X‐ray spectroscopy (WDX) and X‐ray photoelectron spectroscopy (XPS). [ 7,8 ] These results have shown that the Mo:S ratio is ≈1:2.…”
Section: Resultsmentioning
confidence: 77%
“…The electrodeposition experiments were performed in CH 2 Cl 2 solvent using [N n Bu 4 ] 2 [MoS 4 ], which was synthesized in‐house to function as a single source precursor, providing both the Mo and S. [ 7,8 ] In contrast to [NH 4 ] 2 [MoS 4 ], which has been used in aqueous solvents, [N n Bu 4 ] 2 [MoS 4 ] has excellent solubility in CH 2 Cl 2 . The electrodeposition solution also included [N n Bu 4 ]Cl as the supporting electrolyte and trimethylammonium chloride [NHMe 3 ]Cl as the proton source, which is necessary to remove the excess S during deposition of MoS 2 from [MoS 4 ] 2– .…”
Section: Fabrication and Electrodepositionmentioning
confidence: 99%
See 3 more Smart Citations